Project Report on Client Servicing at ABEC (2022-24) Under the Guidance of Prof. Ameya Ambulkar - Vibhute, Kshama (ATLAS SkillTech University, 2024)
The client servicing internship was a transforming experience that gave me the skills and knowledge I needed to succeed in professions that focus on serving clients. The practical experience and knowledge gained during this time will surely help one succeed in the dynamic sector of client servicing and similar industries in the future.
Project Report on Client Servicing at ABEC (2022-24) Under the Guidance of Prof. Ameya Ambulkar
Keywords: Clients; Serving Clients; Knowledge; Client Services